A study of clinical presentation, diagnostic difficulties and various treatment modalities of liver abscess - Dangi, Sunil Kumar; Kulhari, Ashok; Parmar, Ashok; ., Ankita (International Surgery Journal, 2018)
Background: Liver abscess is an uncommon entity and over past 100 years dramatic changes in demographics, etiology, diagnosis and treatment occurred. The purpose of this study was to determine the clinico-etiological demographic profile of liver abscess by using radiological studies and to evaluate the outcome associated with different treatment strategies. Methods: A prospective study was conducted over a cohort of 50 patients presenting with liver abscess. Patients diagnosed with malaria, enteric fever, pyrexia of unknown origin, acute viral hepatitis, chronic liver diseases, or hepatomegaly due to any cause, were excluded from study. Results: The amebic liver abscess was found in 32 patients and pyogenic abscess in 18 patients. The age group ranges from 16 to 78 years with mean age of 38 years and the peak incidence is found in the 31-40 years age group for both types. The M: F ratio is 7:2 in pyogenic liver abscess and 13:3 in amebic. In the present study, the most common symptoms in both types of liver abscess were pain abdomen, loss of weight, anorexia, chills and rigor, vomiting and cough. The most common signs seen in both type liver abscess were tenderness, hepatomegaly and jaundice. In both types liver abscess, right lobe was affected more commonly, and single abscess was more common. Hb <10 gm % is present in more than 50 % cases in both liver abscesses. The right dome of diaphragm elevation present in 75%-89% in both types of liver abscess. In pyogenic liver abscess group, patient had associated intra-abdominal infections. In amebic liver abscess group associated illness was not seen. Antibiotics alone used for small multiple abscesses and antibiotics with needle aspiration done for large abscess, are the main line of treatment in this series. Mortality was nil in present series. Conclusions: Liver abscesses are more common in males, alcoholics and immune-compromised patients. Percutaneous drainage with antibiotics treat majority of cases. The mortality from liver abscess has decreased but incidence appears to be increasing.